Nano optical tweezers generation used for heat surgery of a human tissue cancer cells using add/drop interferometer system - Amiri, I. S. (2013)
A system of add/drop can be used as an interferometer system to generate nano bandwidth of optical tweezers. Dark soliton-Gaussian control within the proposed system is analyzed. Optical tweezers have the unique ability to trap and manipulate particles at the mesoscopic scale. The proposed system can be applied to generate nano-sized bandwidth peaks of optical tweezers in the form of potential wells. The dynamic behavior of the tweezers occurred when the Gaussian laser pulse is added into the system. Here, tweezers with Full Width at Half Maximum (FWHM) of 12 nm could be generated. This technique is applicable for cellular surgery due to the precise setting and small diameter of the nano tweezers. Therefore, the interaction of the nano tweezers with injected gold nano particles contributes to transferring of heat to the abnormal cells leads to removal surgery process, thus tweezers can be used to selectively eliminate cellular components in individual cells.